PENGARUH AKUNTABILITAS PUBLIK, KEJELASAN SASARAN ANGGARAN, DESENTRALISASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA MANAJERIAL DI SKPD KABUPATEN BENGKALIS - Rizky Darmawan; Nur Azlina; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to determine the effect of public accountability, budget goal clarity, decentralization and the internal control system of managerial performance in SKPD Bengkalis. The population in this study are civil servants who have a structural position and officers who have a role in budgeting at every SKPD in government Bengkalis spread over 36 SKPD. Determination of the sample in this study using purposive sampling method that meets the criteria for the election of the desired research. The sample in this study is a government employee who was in the finance department which consists of a head of the division / Head of finance, treasurer and finance department staff totaling 83 people. Analysis of the data used is multiple regression (multiple regression) assisted with SPSS Windows Ver 20. The results of this study prove that public accountability, budget goal clarity, decentralization and the internal control system influence on managerial performance in SKPD Bengkalis.Keywords: Public Accountability, Budget Goal Clarity, Decentralization, Internal Control System, and Managerial Performance